2003
DOI: 10.1099/mic.0.26540-0
|View full text |Cite
|
Sign up to set email alerts
|

The CepIR quorum-sensing system contributes to the virulence of Burkholderia cenocepacia respiratory infections

Abstract: The cepIR genes encode an N-acyl homoserine lactone (AHL)-dependent quorum-sensing system consisting of an AHL synthase that directs the synthesis of N-octanoyl-L-homoserine lactone (OHL) and N-hexanoyl-L-homoserine lactone and a transcriptional regulator. The virulence of cepIR mutants was examined in two animal models. Rats were infected with agar beads containing Burkholderia cenocepacia K56-2, K56-I2 (cepI : : Tp r ) or K56-R2 (cepR : : Tn5-OT182). At 10 days post-infection, the extent of lung histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 56 publications
9
131
0
Order By: Relevance
“…CepI/R CciI/R C6-HSL, C8-HSL Virulence functions and biofilm formation (Malott et al, 2005;Sokol et al, 2003) Erwinia carotovora…”
Section: Burkholderia Cenocepaciamentioning
confidence: 99%
“…CepI/R CciI/R C6-HSL, C8-HSL Virulence functions and biofilm formation (Malott et al, 2005;Sokol et al, 2003) Erwinia carotovora…”
Section: Burkholderia Cenocepaciamentioning
confidence: 99%
“…They have the capacity of spreading between patients and lead determined (Holden et al, 2009). Although the pathogenesis of Bcc is not well understood, a few virulence factors, such as two quorum-sensing systems (Sokol et al, 2003), iron acquisition via siderophore production (Visser et al, 2004), exopolysaccharide synthesis (Moreira et al, 2003) and a type III secretion system (Tomich et al, 2003), have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…For human and plant pathogens, AHL-based communication systems allow a microbial community to strategically induce or repress expression of genes, specifically alleles encoding putative virulence factors, in response to environmental stimuli. Several reports have identified functional QS systems in various Burkholderia species and have shown that these bacterial communication networks both positively and negatively regulate numerous extracellular virulence factors in addition to contributing to animal pathogenicity (B. cepacia) (1,3,20,21,31,34,36).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these Burkholderia QS networks have been shown to both positively and negatively regulate various cellular processes, including AHL and protease production, siderophore biosynthesis, biofilm formation, lipase and betahemolytic activities, swarming and twitching motilities, and substrate utilization (18,20,21,32,35,36). Furthermore, disruption of these cell signaling systems has been shown to reduce the pathogenicity of B. cepacia and Burkholderia pseudomallei in murine and hamster models of infection (1,31,34,36).…”
mentioning
confidence: 99%